Energy security : an interdisciplinary approach - Bahgat, Gawdat; Bahgat, Gawdat (Chichester, U.K. : John Wiley & Sons, 2011)
'This book is split into four parts. Part I introduces the reader to the topic of energy security by providing a theoretical framework. It addresses climate change and gives a balanced view of both producers' and consumers' perspectives. Part II addresses energy security from consuming countries' perspective. There are chapters dedicated to the United States, the European Union, china, India, and Japan. Each examines the diversification of energy mix and energy sources, public institutions in charge of governing energy issues, and laws and other legislations that promote energy security and protect the environment. The next chapter will focus on the role the International Energy Agency has played in coordinating policy between nations. Part III addresses energy security from producing nations' perspective. Chapters cover the Middle East, Africa, Russia, and the Caspian Sea. These examine how producing regions seek to secure a steady income and stable revenues. This section will also discuss national oil companies and their cooperation/confrontation with international companies. The last chapter in this section will focus on the role the Organization of Petroleum Exporting Countries (OPEC) plays in promoting cooperation among major oil producers.The concluding chapter will address the joint efforts by consumers and producers to stabilize global energy markets and the different forums to promote such cooperation (i.e. International Energy Forum). The chapter will also provide a summary of the main findings of the study (i.e. the similarities and differences between the case-studies). Part IV concludes the book with a section on international energy outlook and information on the International Energy Forum'--Provided by publisher.
'This rising demand has further deepened the international competition over fossil fuel deposits and underscored the need to comprehensively and adequately address the quest for energy security'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Energy policy; Energy development; Power resources